Teachers’ model for teaching critical thinking in primary school - Kamarulzaman, Wirawani; Mohd Jodi, Khairul Hamimah; Oo, Cheng Keat; Mahmood, Rosinah; Che Aziz, Raziana (Academia Industry Networks, 2021)
The general purpose of this study is to investigate the applicability of the teachers’ model for critical thinking in primary school to several selected schools. The model suggested several steps need to be fulfilled to promote critical thinking in the classroom. Thus, the study employed 25 primary school teachers to investigate their understanding of critical thinking skills and their techniques for teaching the skills. A training was given to teachers to help them improve their teaching techniques. Findings revealed that teachers understood the concept and were able to infuse the techniques in their teaching. They believed that the techniques were not new, but after the training, they are able to teach the skills more systematically. This shows that the model can be used in exploring the promotion of critical thinking and primary school classroom.